The Effects of Chromium Picolinate and Chromium Histidinate Administration on NF-?B and Nrf2/HO-1 Pathway in the Brain of Diabetic Rats - Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Gencoglu, Hasan; Ulas, Mustafa; Atalay, Mustafa; Komorowski, James R. (Humana Press Inc, 2012)
The objective of this experiment was to investigate the effects of supplemental chromium picolinate (CrPic) and chromium histidinate (CrHis) on nuclear factor-kappa B (NF-kappa B p65) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2) signaling pathway in diabetic rat brain. Nondiabetic (n = 45) and diabetic (n = 45) male Wistar rats were either not supplemented or supplemented with CrPic or CrHis via drinking water to consume 8 mu g elemental chromium (Cr) per day for 12 weeks. Diabetes was induced by streptozotocin injection (40 mg/kg i.p., for 2 weeks) and maintained by high-fat feeding (40 %). Diabetes was associated with increases in cerebral NF-kappa B and 4-hydroxynonenal (4-HNE) protein adducts and decreased in cerebral nuclear factor of kappa light polypeptide gene enhancer in B cells inhibitor, alpha (I kappa B alpha) and Nrf2 levels. Both Cr chelates were effective to decrease levels of NF-kappa B and 4-HNE protein adducts and to increase levels of I kappa B alpha and Nrf2 in the brain of diabetic rats. However, responses of these increases and decreases were more notable when Cr was supplemented as CrHis than as CrPic. In conclusion, Cr may play a protective role in cerebral antioxidant defense system in diabetic subjects via the Nrf2 pathway by reducing inflammation through NF-kappa B p65 inhibition. Histidinate form of Cr was superior to picolinate form of Cr in reducing NF-kappa B expression and increasing Nrf2 expression in the brain of diabetic rats.
Keywords: Chromium picolinate/histidinate; NF-kappa B p65; I kappa B alpha; Nrf2